1995
DOI: 10.1148/radiology.194.1.7997553
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic manifestations of Behçet syndrome: radiographic and CT findings in nine patients.

Abstract: Chest radiographic findings of thoracic Behçet syndrome are variable and nonspecific. CT can be helpful in the assessment of the syndrome by showing thrombosis of the superior vena cava and characteristic aneurysms of the pulmonary arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 0 publications
3
25
0
Order By: Relevance
“…Parenchymal opacity and, in particular, airspace consolidation observed on chest radiography or CT was previously reported to be an indication of pulmonary infarction in the clinical setting [5,29]. Thus, our observations on thoracic CT scans of animals with photodynamically induced infarction are in accord with clinical findings.…”
Section: Model Of Targeted Pulmonary Infarctionsupporting
confidence: 89%
See 1 more Smart Citation
“…Parenchymal opacity and, in particular, airspace consolidation observed on chest radiography or CT was previously reported to be an indication of pulmonary infarction in the clinical setting [5,29]. Thus, our observations on thoracic CT scans of animals with photodynamically induced infarction are in accord with clinical findings.…”
Section: Model Of Targeted Pulmonary Infarctionsupporting
confidence: 89%
“…Pulmonary embolism is more frequently associated with lung infarction in lung transplant recipients (37.5%), probably due to the absent or poorly developed collateral bronchial circulation [4]. Other conditions, such as vasculitis, angioinvasive infections, and sickle cell disease, can also lead to pulmonary infarction [5]. Pulmonary infarction is also a frequent complication in immunocompromised patients with pulmonary aspergillosis, often resulting in fatal consequences [6,7].…”
mentioning
confidence: 99%
“…6 Pulmonary artery aneurysms may manifest as hilar enlargement or round, lobulated opacities on chest radiographs. 16 Computed tomography has largely replaced angiography as the diagnostic tool and magnetic resonance imaging can also be useful for diagnosis of PAAs, but appears to be less sensitive than computed tomography for diagnosis of small PAAs. 2 Erkan et al 2 reported that PAAs are most often located in the right lower lobar arteries, followed by bilateral main pulmonary branches.…”
Section: Discussionmentioning
confidence: 99%
“…(6) In addition, small sample size is a problem inherent to studies of rare manifestations of lowprevalence diseases. (4,5,17,18) In summary, patients with Behcet's diseaserelated pulmonary involvement can present good survival with appropriate immunosuppressive therapy. In addition, Behcet's disease must be recalled as a cause of alveolar hemorrhage and pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been no randomized controlled studies evaluating these options in treatment, and only a few case series have been published on the topic. (3)(4)(5) A recent cumulative analysis suggested good survival in patients receiving immunosuppressive therapy. (6) The aim of this study was to analyze clinical and tomographic evolution, as well as the survival, of patients with Behcet's disease-related pulmonary involvement treated at our facility, all of whom received immunosuppressive therapy.…”
Section: Introductionmentioning
confidence: 99%